3-Difference cordial labeling of some path related graphs - R Ponraj; M Maria Adaickalam; R Kala (Indonesian Journal of Combinatorics, 2018)
Let G be a (p, q)-graph. Let f : V(G) → {1, 2, …, k} be a map where k is an integer, 2 ≤ k ≤ p. For each edge uv, assign the label ∣f(u) − f(v)∣. f is called k-difference cordial labeling of G if ∣vf(i) − vf(j)∣ ≤ 1 and ∣ef(0) − ef(1)∣ ≤ 1 where vf(x) denotes the number of vertices labelled with x, ef(1) and ef(0) respectively denote the number of edges labelled with 1 and not labelled with 1. A graph with a k-difference cordial labeling is called a k-difference cordial graph. In this paper we investigate 3-difference cordial labeling behavior of triangular snake, alternate triangular snake, alternate quadrilateral snake, irregular triangular snake, irregular quadrilateral snake, double triangular snake, double quadrilateral snake, double alternate triangular snake, and double alternate quadrilateral snake.